2016
DOI: 10.1007/s00192-016-3080-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and degree of bother of pelvic floor disorder symptoms among women from primary care and specialty clinics in Lebanon: an exploratory study

Abstract: In this convenience sample of Lebanese women, PFD symptoms were common and were significantly correlated with demographic characteristics and self-reported comorbidities. The key reason for not seeking health care related to PFD was financial concern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 25 publications
2
28
0
Order By: Relevance
“…The presence of PFMD has also been found in other studies in the literature, being more prevalent in overweight or obese women over 40 years of age [17,30,31]. Although, in the present study, the participants were young, Ghandour et al [32], in a study with 900 women, found a greater presence of PFMD in women over 60 years of age and in overweight women, suggesting such conditions to be a risk factor for PFMD.…”
Section: Discussionsupporting
confidence: 84%
“…The presence of PFMD has also been found in other studies in the literature, being more prevalent in overweight or obese women over 40 years of age [17,30,31]. Although, in the present study, the participants were young, Ghandour et al [32], in a study with 900 women, found a greater presence of PFMD in women over 60 years of age and in overweight women, suggesting such conditions to be a risk factor for PFMD.…”
Section: Discussionsupporting
confidence: 84%
“…Age, vaginal delivery, and higher parity were found to be the risk factors associated with the development of PFD. A recent study on Lebanese women visiting clinics in a University Medical Center in Beirut [ 48 ] reported a 34.6% prevalence of obstructed defecation. Pelvic Floor Bother Questionnaire (PFBQ) scores were found to be significantly higher in those who had ≥ 3 vaginal deliveries.…”
Section: Consensus Statementsmentioning
confidence: 99%
“…10 However, the relationship between PFMD and obesity indicators is better known in the literature in middle-aged and elderly women. 5,6,9 This was reported by Lai et al, 11 who observed that the odds of having urinary stress incontinence increased by 1.27 times every 10 cm increase in WC and 1.32 times for every 5 units of BMI increase in women with a mean age of 59.1 years.…”
mentioning
confidence: 65%